PENGEMBANGAN SISTEM DATABASE SUMBER DAYA AIR KOTA SAMARINDA - Heru Dwi Wahjono (Jurnal Teknologi Lingkungan, 2007)
In order to manage region water resources, Samarinda City has been collecting and managing all data of water resources. Good data management for water resources is needed to maintain water potential and suplay for this city and to control water quality from environmental pollution. The management of the existing water resources is needed by developing computer base structural database management system. The design of database system is used for development of software for water resources database management. The developed software can be used as Decision Support System to help city management and useful for information system to find out the potential of all water resources in Samarina. The output of this activity is software formanaging water resources in Samarinda city.